Effect of Secukinumab on Patient‐Reported Outcomes in Patients With Active Ankylosing Spondylitis: A Phase III Randomized Trial (MEASURE 1). Issue 12 (December 2016) - Deodhar, Atul A.; Dougados, Maxime; Baeten, Dominique L.; Cheng‐Chung Wei, James; Geusens, Piet; Readie, Aimee; Richards, Hanno B.; Martin, Ruvie; Porter, Brian
Abstract : Objective: To evaluate the effect of secukinumab (interleukin‐17A inhibitor) on patient‐reported outcomes in patients with active ankylosing spondylitis (AS). Methods: In this phase III study, 371 patients were randomized (1:1:1) to receive intravenous (IV) secukinumab 10 mg/kg at baseline and weeks 2 and 4 followed by subcutaneous (SC) secukinumab 150 mg every 4 weeks (IV→150 mg group), or SC secukinumab 75 mg every 4 weeks (IV→75 mg group), or placebo. Patient‐reported outcomes included the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), BASDAI criteria for 50% improvement (BASDAI 50), Short Form 36 (SF‐36) physical component summary (PCS) score and mental component summary (MCS) score, Ankylosing Spondylitis Quality of Life (ASQoL) questionnaire, Bath Ankylosing Spondylitis Functional Index (BASFI), EuroQol 5‐domain (EQ‐5D) questionnaire, Functional Assessment of Chronic Illness Therapy–Fatigue (FACIT‐F), and Work Productivity and Activity Impairment–General Health questionnaire (WPAI‐GH). Results: At week 16, secukinumab IV→150 mg or IV→75 mg was associated with statistically and clinically significant improvements from baseline versus placebo in the BASDAI (−2.3 for both regimens versus −0.6; P < 0.0001 and P < 0.001, respectively), SF‐36 PCS (5.6 for both regimens versus 1.0; P < 0.0001 and P < 0.001, respectively), and ASQoL (−3.6 for both regimens versus −1.0; P < 0.0001 and P < 0.001, respectively). Clinically significant improvements in the SF‐36 MCS, BASFI, EQ‐5D, and BASDAI 50 were observed with both secukinumab groups versus placebo at week 16; improvements were also observed in the FACIT‐F and WPAI‐GH. All improvements were sustained through week 52. Conclusion: Our findings indicate that secukinumab provides significant and sustained improvements in patient‐reported disease activity and health‐related quality of life, and reduces functional impairment, fatigue, and impact of disease on work productivity in patients with active AS.